2022
DOI: 10.1007/s00198-022-06329-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different exercise intensity on bone mineral density in adults: a comparative systematic review and meta-analysis

Abstract: Purpose The primary objective of the present systematic review and meta-analysis was to determine the effect of differing exercise intensity on (areal) bone mineral density (BMD) at lumbar spine and hip in adults by a comparative meta-analysis. Methods A systematic review of the literature according to the PRISMA statement included: (a) exercise trials, (b) with ≥two study arms that compared different exercise intensities, (c) intervention ≥6 months, (d) BMD assessments at lumbar spine (LS) or hip. Five electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
5
0
3
Order By: Relevance
“…One solution to this problem might be comparative meta-analyses that include trials with two study arms with diverging exercise parameters (e.g. intensity [ 122 ] or training frequency [ 119 ]) but otherwise identical protocols (… and participants).…”
Section: Discussionmentioning
confidence: 99%
“…One solution to this problem might be comparative meta-analyses that include trials with two study arms with diverging exercise parameters (e.g. intensity [ 122 ] or training frequency [ 119 ]) but otherwise identical protocols (… and participants).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several controversies are still open about the macroscopical effects of physical exercise on BMD, and previous systematic reviews and meta-analyses reported insufficient evidence to support a superior effect of one specific exercise modality [ 67 , 68 ]. However, it should be noted that the currently available literature focused on standardized exercise programs without focusing on the biological effects of physical exercise in an individualized rehabilitation plan.…”
Section: Discussionmentioning
confidence: 99%
“…One may argue that this approach might not identify all eligible reports or studies. However, one should bear in mind that this study was conducted within the framework of the (German) National guideline of fracture prevention that is based on several systematic reviews and meta-analyses in the area of exercise and BMD (e.g., [ 4 , 11 , 12 , 42 ]). Using synergy effects between the searches and considering the close interaction between the researchers, we are very confident that all eligible studies have been included in the present work.…”
Section: Discussionmentioning
confidence: 99%